Gender, labour, and Migration: Categories for the Study of the Republican Exile of 1939 in France (2024)
This article analyzes women from the Spanish Republican exile of 1939 to France through a case study, examining migrations and exiles from a gender perspective. Migration and refugee movements pose contemporary challenges that need to be understood historically. We observe that labour integration into host societies is one of its most critical aspects, and it also has its own gender dimension. Therefore, we will explore how migration studies in history have examined the relationship between gender and labour, proving to be valuable in revealing the agency of migrant women. Finally, we will critically review the historiography concerning women in the Republican exile of 1939 and the gaps that persist regarding the labour dimension of their experiences, offering some interpretations and suggesting future lines of research.